Pemanfaatan Pupuk Organik Cair Kulit Buah Pisang untuk Pertumbuhan Bibit Pinang (Areca catechu L.) - Yuliani, Tri; Yetti, Husna; Yulia, Arnis En (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the effect of liquid organic fertilizer application of banana fruit peel and get the best dose for the growth of areca seedlings. This research was conducted at experiment station of agriculture faculty of University of Riau from July to November 2017. This research was conducted in the form of experiment using completely non-factorial randomized designconsisting of 5 levels and 4 replications. The liquid organic fertilizer of banana fruit peel consists of 0, 250, 500, 750, 1000 ml.10 kg-1 medium. Data have been statistically analyzed and examined further with using the duncan's new multiple range test (DNMRT) at 5% level. The results showed that increased dosage of liquid organic fertilizer banana fruit peel increased the accretion height of seedlings, dry weight and shoot root ratio, but no increase the leaf number accretion, stem circumference and widest leaf area.The dosage of liquid organic fertilizer of banana fruit peel of 750 ml.10 kg-1 medium gives the increase of accretion height seedlings, dry weight and the highest shoot root ratio in 6 month old areca seedlings.Keyword : Seedlings, liquid organic fertilizer of banana fruit peel, growthÂ